Kedudukan Notaris dalam Pembuatan Akta terhadap Rapat Umum Pemegang Saham yang Diadakan melalui Media Telekonferensi - I Made Nova Wibawa; I Nyoman Alit Puspadma; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2021)
The Law No 40 of 2007 concerning PT (Limited Liability Company) regulates what can be done through teleconferencing media regulated in Article 77 paragraph (1) of Company Law so as to allow shareholders to conduct a GMS without having to meet in person and be in one place but can be held by teleconference which allows shareholders to see each other and interact actively in meetings The results of the minutes of the GMS held by the PT are not required to be written in the form of an authentic deed meaning that the PT can determine the agreement of the shareholders whether it will be written into an authentic deed or an underhand deed The minutes of the GMS by teleconference which are applied to the authentic deed by the Notary lose their authenticity because the Notary does not act according to the provisions in Article 16 paragraph (1) letter m UUJN-P which requires the physical presence of the parties in the process of drafting an authentic deed so that the power of proof of the deed under the hand as a result of an act that is not in accordance with Article 16 paragraph (1) letter m.